News Stories of Intimate Partner Violence: An Experimental Examination of Media Framing and Perpetrator Sex in LGBTQ Versus Heterosexual Relationships - Savage, Matthew W. (Journal of interpersonal violence, 2022)
This study experimentally examines the effects of perpetrator sex (male or female), relationship context (heterosexual or homosexual), and the type of media framing (episodic or thematic) on endorsement for public health perspectives about intimate partner violence (IPV) and punishment preferences for IPV perpetrators. Participants (N = 750) were randomly assigned to a condition, exposed to a composite news story, and then completed a survey. Manipulation check responses demonstrated a pattern suggesting that participants had difficulty attending to details of IPV in stories where the perpetrator was a woman, or where the violence occurred in a homosexual relationship. Results revealed significant interaction effects for the endorsement of public health perspectives and for perpetrator punishment preferences. Results for the endorsement of public health perspectives showed that thematic framing caused stronger support only when the perpetrator was a heterosexual man. Results for perpetrator punishment preferences revealed a pattern where participants preferred stronger punishments for heterosexual male perpetrators over any other group. Participants did not distinguish in their punishment preferences for male or female homosexual perpetrators, but these were still stronger than their punishment preferences for heterosexual female perpetrators. Theoretical implications are presented with attention to extending research about media portrayals of IPV, and discussion is offered concerning practical considerations for public health support services that address IPV.